Harmonizing Modernity with Tradition: Report on Indonesian Delegation of Teachers and Pesantren Heads to Japan 2007 - Subhan, Arief (Studia Islamika, 2008)
The 2007 visit was themed "Development Harmonized with Traditional Culture". As well as visiting a number of education institutions, which was the focus of the trip, the group also took a look at various types of Japanese industry, including the automotive industry that has become the icon of modern Japan. On the final day of the visit, the participants were asked to write about their impressions of Japan, with emphasis on the aspect of the tour which they found to be most interesting. This article, which is based on feedback from the participants, has not been written only in order to describe the perceptions of the participants towards places visited throughout the tour, but to further discuss how the participants gave meaning to what they experienced throughout the trip.DOI: 10.15408/sdi.v15i1.541